Analisis Semiotika Representasi Komunikasi Keluarga Dalam Film Ngeri-Ngeri Sedap - Sinuraya, July Susanti Br (CV. ITTC INDONESIA, 2023)
This research is entitled Semiotic Analysis of Family Communication Representation in the Horrific-Ngeri Savory Film. The purpose of this study is to find out how the Semiotic Analysis of Family Communication Representation in the Horrific-Ngeri Sedap Film is. The theory used to explore this research is the theory of semiotics. The object of his research is the Horrifying-Horrifying Film. The method used in this study is a qualitative method with Roland Barthes' model of semiotic analysis techniques. The results of the study show that there are several scenes depicting representations of family communication.